Odpowiedź :
1.
[tex]1 - \frac{1}{3} = \frac{2}{3} [/tex]
[tex]1 - \frac{2}{3} = \frac{1}{3} \\ \\ \frac{1}{3} + \frac{2}{3} = 1[/tex]
2.
a)
[tex]1 - \frac{3}{7} = \frac{4}{7} [/tex]
b)
[tex]1 - \frac{3}{4} = \frac{1}{4} [/tex]
c)
[tex]2 - \frac{4}{5} = 1 \frac{1}{5} [/tex]
3.
[tex]1 \frac{2}{3} - \frac{1}{3} = 1 \frac{1}{3} [/tex]
[tex]3 \frac{4}{5} - 2 \frac{3}{5} = 1 \frac{1}{5} [/tex]
[tex]5 \frac{5}{7} - 2 \frac{2}{7} = 3 \frac{3}{7} [/tex]
3.
1-1/3=2/3
1-2/3=1/3 bo 1/3+2/3=1
4.
a)1-3/7=4/7
b)1-3/4=1/4
c)2-4/5=1 1/5
5.
a)1 2/3-1/3= 1 1/3
b)3 4/5-2 3/5=1 2/5
c) 5 5/7-2 2/7= 3 3/7
1-1/3=2/3
1-2/3=1/3 bo 1/3+2/3=1
4.
a)1-3/7=4/7
b)1-3/4=1/4
c)2-4/5=1 1/5
5.
a)1 2/3-1/3= 1 1/3
b)3 4/5-2 3/5=1 2/5
c) 5 5/7-2 2/7= 3 3/7